Double perovskites La2MMnO6 as catalyst for propane combustion - Tasca, Julia Elena (2017)
The synthesis, structural, spectroscopic and morphological characterization; as well as the evaluation of the catalytic properties, of a family of oxides La2MMnO6, with M = Co, Ni and Cu are presented in this work. The materials were obtained by solid state reaction and through citrate route. The structure was determined by X-ray diffraction and a correlation was found between the crystal cell parameters and the M(II) cation sizes, as a consequence of MO6 and MnO6 octahedral ordering. According to infrared spectroscospic characterization of the materials prepared by citrate route, a diminution of the M4+-O bond strength was observed, according with M(II) sizes, in the sequence: Cu > Ni > Co. More labile O species should be present in La2CoMnO6-CIT. The electron microscopy morphology of this oxide confirmed the presence of agglomerated tiny particles. The presence of nanometic crystallites was confirmed by transmission electron microscopy. The catalytic tests, using propane as reaction test, were carried out in a fixed bed micro reactor, coupled with an “on line” chromatograph. The materials obtained by citrate route, despite M(II) cations, are better suited for propane combustion and the catalyst La2CoMnO6 is the most active of the investigated series with T90 ∼ 500 °C.